A Local Search Algorithm for the Flow Shop Scheduling Problem with Release Dates - Tao Ren; Meiting Guo; Lin Lin; Yunhui Miao (Discrete Dynamics in Nature and Society)
This paper discusses the flow shop scheduling problem to minimize the makespan with release dates. By resequencing the jobs, a modified heuristic algorithm is obtained for handling large-sized problems. Moreover, based on some properties, a local search scheme is provided to improve the heuristic to gain high-quality solution for moderate-sized problems. A sequence-independent lower bound is presented to evaluate the performance of the algorithms. A series of simulation results demonstrate the effectiveness of the proposed algorithms.